2020
DOI: 10.1007/s40544-020-0450-8
|View full text |Cite
|
Sign up to set email alerts
|

Nanolubricant additives: A review

Abstract: Using nanoadditives in lubricants is one of the most effective ways to control friction and wear, which is of great significance for energy conservation, emission reduction, and environmental protection. With the scientific and technological development, great advances have been made in nanolubricant additives in the scientific research and industrial applications. This review summarizes the categories of nanolubricant additives and illustrates the tribological properties of these additives. Based on the compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(93 citation statements)
references
References 181 publications
0
75
0
3
Order By: Relevance
“… 53 In addition, ZrP, a widely applied nanolubricant additive, could repair scars and grooves of a material surface via surface repairing and polishing effect, which in turn could considerably enhance friction resistance. 54 , 55 Another study claimed that after doping ZrP nanosheets in polyvinyl alcohol, its nano-mechanical properties, such as hardness and elastic modulus, were improved. 56 Therefore, we believed that although the ZrP coating did not effectively change the COF of SLA, its layered structures and superior hardness/elastic modulus would play a direct role in the wear process, resulting in a significant decrease in wear area and wear rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 53 In addition, ZrP, a widely applied nanolubricant additive, could repair scars and grooves of a material surface via surface repairing and polishing effect, which in turn could considerably enhance friction resistance. 54 , 55 Another study claimed that after doping ZrP nanosheets in polyvinyl alcohol, its nano-mechanical properties, such as hardness and elastic modulus, were improved. 56 Therefore, we believed that although the ZrP coating did not effectively change the COF of SLA, its layered structures and superior hardness/elastic modulus would play a direct role in the wear process, resulting in a significant decrease in wear area and wear rate.…”
Section: Resultsmentioning
confidence: 99%
“… 56 Therefore, we believed that although the ZrP coating did not effectively change the COF of SLA, its layered structures and superior hardness/elastic modulus would play a direct role in the wear process, resulting in a significant decrease in wear area and wear rate. 54–57 …”
Section: Resultsmentioning
confidence: 99%
“…NPs with a sphere, quasi-spherical, or hemispherical shape play this role. Generally, spherical NPs reduce the COF by converting sliding friction to rolling friction as a result of their morphological properties [233][234][235]. Some scholars have revealed that these NPs themselves might roll or embed into surfaces [236][237][238].…”
Section: Rolling/ball Bearing Effectmentioning
confidence: 99%
“…Therefore, the lubricating oil must maintain low-friction property across a wide temperature range. However, most lubricants begin to thermally degrade and oxidize at high-temperature, resulting in a loss of original lubrication performance (Wang et al , 2020; Zhao et al , 2021).…”
Section: Introductionmentioning
confidence: 99%